A new context for urban design: the role of drawing in the design process - Ana Paula Rainha (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The composition of urban space today seems to be considered a less important issue in the practice of city development. The impoverishment process of the formal and compositional components of the urban spaces is more evident when the several and necessary knowledges in planning are contemplated and understood. These aspects imply a reflection on essential aspects of urban concerns which are mainly related to the formal composition, based on the experimentation and on the individual creativity of the designer. This paper pretends an approach to the relevance of this subject for the urban planning, through its various phases from XV century until now, focusing on the role of the free drawing in the urban design process, concluding with its importance at several levels for the urban planning and cities development.